Concise Enantioselective Syntheses of (+)-L-733,060 and (2S,3S)-3-Hydroxypipecolic Acid by Cobalt(III)(salen)-Catalyzed Two-Stereocenter Hydrolytic Kinetic Resolution of Racemic Azido Epoxides - Devalankar, Dattatray A.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Synlett, 2014)
An efficient synthesis of the 2,3-disubstituted piperidines (+)-L-733,060 and (2S,3S)-3-hydroxypipecolic acid (≥99% ee) in high optical purity from commercially available starting materials is described. The strategy involves a cobalt-catalyzed hydrolytic kinetic resolution of a racemic azido epoxide with two stereocenters and an intramolecular reductive cyclization as key reactions.
Keywords: azides; epoxides; stereoselective synthesis; Wittig reactions; cyclizations; piperidines